Cold War Britain
IX, 244 p.
Keywords: Britain and the Cold War, 1945-1964 offers new perspectives on ways in which Britain fought the Cold War, and illuminates key areas of the policy formulation process. It argues that in many ways Britain and the United States perceived and handled the threat posed by the Communist bloc in similar terms: nevertheless, Britain's continuing global commitments, post-war economic problems and somestic considerations obliged her on occasion to tackle the threat rather differently.